2009
DOI: 10.1371/journal.pntd.0000553
|View full text |Cite|
|
Sign up to set email alerts
|

Mycolactone Gene Expression Is Controlled by Strong SigA-Like Promoters with Utility in Studies of Mycobacterium ulcerans and Buruli Ulcer

Abstract: Mycolactone A/B is a lipophilic macrocyclic polyketide that is the primary virulence factor produced by Mycobacterium ulcerans, a human pathogen and the causative agent of Buruli ulcer. In M. ulcerans strain Agy99 the mycolactone polyketide synthase (PKS) locus spans a 120 kb region of a 174 kb megaplasmid. Here we have identified promoter regions of this PKS locus using GFP reporter assays, in silico analysis, primer extension, and site-directed mutagenesis. Transcription of the large PKS genes mlsA1 (51 kb),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 49 publications
4
43
2
Order By: Relevance
“…Our findings on M. ulcerans in mosquito larvae are in partial agreement with recent reports from Australia (43). Both studies provide evidence for the survival of M. ulcerans in mosquito larvae.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings on M. ulcerans in mosquito larvae are in partial agreement with recent reports from Australia (43). Both studies provide evidence for the survival of M. ulcerans in mosquito larvae.…”
Section: Discussionsupporting
confidence: 93%
“…In the Australian study, the infection was not studied throughout the mosquito developmental cycle. One difference between our work and that of Tobias et al (43) is that Tobias found that M. ulcerans survived much better in Aedes comptorhynchus mosquito larvae than did a nonpigmented variant of the closely related non-toxin-producing M. marinum species. In contrast, we find that the survival phenotype of WT M. marinum in Aedes aegypti mosquito larvae is identical to that of M. ulcerans; both species survived in high numbers throughout the larval developmental cycle.…”
Section: Discussioncontrasting
confidence: 85%
“…Real-time PCR was performed on M. ulcerans strains to estimate cell numbers as previously described [28]. Primers targeting the 16S rRNA gene were used for detection of mycobacteria.…”
Section: Methodsmentioning
confidence: 99%
“…ulcerans strains and inoculation M. ulcerans strain nos. 01G897, JKD8083, and S4018 were originally isolated from patients from French Guiana, Australia, and Benin, respectively (22)(23)(24). Bacterial suspensions were prepared as previously described (10), and then adjusted at 2 3 10 5 acid-fast bacilli/ml to be inoculated (50 ml) into the tail of 6-wk-old females of the consanguine BALB/c, C57BL/6, and FVB/N mouse strains (Charles River Laboratories, Saint-Germain-Nuelles, France).…”
Section: Ethics Statement For Animal Experimentsmentioning
confidence: 99%